Multi‐temporal Digital Photogrammetric Analysis for Quantitative Assessment of Soil Erosion Rates in the Landola Catchment of the Upper Orcia Valley (Tuscany, Italy). (27th September 2014) - Aucelli, Pietro P. C.; Conforti, Massimo; Della Seta, Marta; Del Monte, Maurizio; D'uva, Lorenzo; Rosskopf, Carmen M.; Vergari, Francesca
ABSTRACT: This paper focuses on the analysis of the slope and catchment erosion dynamics in a typical Mediterranean context and its sensitivity to recent climatic and socio‐economic changes. The main objective of the present study is to test the reliability of digital photogrammetric analysis to evaluate the time and space evolution of erosion processes mainly triggered by surface running waters and landslides for about the last 60 years. The selected test area is the Landola catchment, a minor tributary of the Upper Orcia River Valley (Southern Tuscany). The Upper Orcia valley is a key site for the comprehension of denudation processes typically acting in Mediterranean badland areas thanks to the following: (i) the availability of long‐lasting erosion monitoring datasets (20 years' long direct measurements at erosion 'hot spots'); (ii) its representativeness as a sub‐humid Mediterranean badland area; and (iii) the rapidity of development of erosion processes, which makes it suitable as an open‐air laboratory for the study of badland dynamics. The outputs of this work highlight that the application of high‐resolution digital photogrammetric methodologies can represent a powerful and low‐cost tool to evaluate rates and spatial–temporal distribution of denudation processes, as confirmed by the validation through field point monitoring in areas close to the study area. The results obtained for the study area confirm that high erosion rates are a persistent environmental problem for the Upper Orcia Valley, which is not solved up to now, despite various land conservation interventions. The performed multi‐temporal analysis shows a slight decrease in the average water erosion rate during the last 60 years and a parallel increase in the frequency of mass wasting events. These variations are most likely related to a complex interplay between land use changes that have affected the study area during the studied period, revealing a very delicate equilibrium between farming activities and erosion processes. Copyright © 2014 John Wiley & Sons, Ltd.